2000
DOI: 10.1093/ajcn/72.1.82
|View full text |Cite
|
Sign up to set email alerts
|

Introducing a new component of the metabolic syndrome: low cholesterol absorption

Abstract: Baseline cholesterol absorption and synthesis were related to respective serum SHBG, glucose, and insulin values. Weight reduction increased cholesterol absorption and improved variables of glucose metabolism. These results suggest that low cholesterol absorption and high synthesis may be part of the insulin resistance syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
125
1
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(145 citation statements)
references
References 33 publications
17
125
1
2
Order By: Relevance
“…The only research found was in subjects with type 2 diabetes mellitus (DM) using plant sterol and cholesterol precursors as indicators of absorption and synthesis. 39,40 Although, both studies indicated a decrease in synthesis and an increase in absorption after weight loss, the methods used only a crude estimation of cholesterol kinetics, as plant sterols and cholesterol precursors might be affected by diet and are not quantitative measures of metabolism. [39][40][41] The use of isotope ratio methodology in this trial offers a more precise quantifiable measure of cholesterol metabolism and, thus, may explain the differences in findings between this and other studies.…”
Section: Discussionmentioning
confidence: 99%
“…The only research found was in subjects with type 2 diabetes mellitus (DM) using plant sterol and cholesterol precursors as indicators of absorption and synthesis. 39,40 Although, both studies indicated a decrease in synthesis and an increase in absorption after weight loss, the methods used only a crude estimation of cholesterol kinetics, as plant sterols and cholesterol precursors might be affected by diet and are not quantitative measures of metabolism. [39][40][41] The use of isotope ratio methodology in this trial offers a more precise quantifiable measure of cholesterol metabolism and, thus, may explain the differences in findings between this and other studies.…”
Section: Discussionmentioning
confidence: 99%
“…2 ApoB isotopic enrichment was measured using GCMS, and production and fractional catabolic rate (FCR) of VLDL apoB was derived using multicompartmental modelling (SAAM-II). Plasma lathosterol and campesterol concentrations were measured by gas-liquid chromatography [5][6][7] and expressed in mmol  10 2 per mol of cholesterol. Data were analysed by analysis of covariance using general linear models.…”
Section: Methodsmentioning
confidence: 99%
“…3,4 Metabolic syndrome patients also have abnormal cholesterol homeostasis, reflected by increased body cholesterol synthesis and decreased cholesterol absorption efficiency. 2,5 Cholesterol absorption efficiency is reflected by the plasma concentrations of plant sterols, particularly campesterol. 6 The therapeutic consequences of inhibiting cholesterol synthesis on both hepatic secretion of apoB and cholesterol absorption have not yet been investigated in the metabolic syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies had shown that higher BMI is associated with decreased LDL-cholesterol responses to hypolipidemic diets [85,86,87]. High cholesterol synthesis and reduced intestinal cholesterol absorption in insulin-resistant states [88,89] might explain these findings, as an enhanced cholesterol flux through the liver will down-regulate LDL receptors and make them refractory to additional regulation by dietary fatty acid changes, while a decreased cholesterol flux though enterocytes would lessen both the cholesterol-raising response to dietary cholesterol and the cholesterol-lowering effect of plant sterols. Nuts are rich in plant sterols, which are likely to contribute to their cholesterol lowering effect [24], but this would be less operative when cholesterol absorption is low.…”
Section: Nut Feeding Trials With Outcomes On Cardiovascular Risk Fmentioning
confidence: 99%